Human security and mutual vulnerability : the global political economy of development and underdevelopment - Nef, Jorge (International Development Research Centre, 1999)
Jorge Nef responds to one of the most pressing intellectual challenges of the post-Cold War era: the search for an analytical framework that will help us understand this turbulent and chaotic period in human history. His lucid and visionary analysis rests on the concept of mutual vulnerability: that in an increasingly interdependent world, global security is only as strong as the weakest link in the chain. This second edition includes new analyses of the economic crisis in Asia, the transformation of the G-7 into the G-8, the easing of the debt crisis, and Soros' critique of the New World Order. Data and sources are also updated, as are the discussions of conflicts in Africa, the former Yugoslavia, and central Asia.